Collaborative platforms for rural innovation: Strengthening farmer organizations for sustainable change - Vanegas Cubillos, Martha; Santamaria, Juliana; Rodriguez, Luz Angela (2024)
This study explores the role of farmer organizations as multi-stakeholder platforms in promoting sustainable, low-emission food systems and improving livelihoods for farmers in the Colombian region of Caquetá. Part of the Low-Emission Food Systems initiative (Mitigate+), the research evaluates local cocoa and livestock organizations to assess their organizational sustainability and capacity to host a Participatory Rural Innovation Process aimed at fostering co-creation of sociotechnical innovations. Using frameworks by Springer-Heinze (2018) and Rondot and Collion (2001), we analyzed six organizations: two cocoa groups (ASPROABELÉN and COMOCAN) and four livestock organizations (ASMEGO, ASOAGROEMPT, ASMUJSAN, ASMUFEM), with AGROSOLIDARIA identified as the best candidate to lead the innovation process.